STUDENTS PROBLEMS OF READING SKILL IN NARRATIVE TEXT AT TENTH GRADE OF SMA KARTIKA PEMATANGSIANTAR - Lumbantungkup, Andina; Sitorus, Mista Adelina; Siahaan, Chatrin Octavia; Hutabarat, Loisa Clara (Transpublika Publisher, 2022)
Reading is one of the four language skills taught in the process of learning English, along with listening, speaking, and writing. Reading is the ability to comprehend the content of a text. Reading can provide readers with all of the messages and information they require. The purpose of this study is to learn about the students’ reading problems at SMA Kartika 1-4 Pematangsiantar as well as to find a solution to the problems. Descriptive qualitative research was performed in this study. The participants in the study were tenth-grade of MIPA 3 students from SMA Kartika Pematangsiantar, who were found to have reading difficulties. The result of this research found that the students’ problem in reading as follow : internal problems (lack of student vocabulary, a lack of student interest in English subjects, boredom and laziness, and a lack of time to study any English text in class.) And external problems (such as the teacher’s method of instruction, students’ lack of personal dictionaries, the narrative text’s level of difficulty and the lack of textbooks). As a solution, the teacher must play an important role in overcoming the problems faced by students by making teaching techniques more interesting and interactive.